Implications of Teacher Emotions on the Motivation of 10th Grade Students Towards Learning English (2023)
This exploratory case study aimed at analyzing the influence of teacher's emotions on the motivation of 10th grade students towards learning a second language in a public school, in Medellin. One English teacher was interviewed on three factors: teacher' emotions towards teaching, the language and students. In addition, 17 students completed a questionnaire that asked for responses to 2 factors: extrinsic and intrinsic motivation. The data analysis led to the conclusion that teachers' emotions can affect the motivation of students; however, the students’ motivation can also affect the attitude of the teacher. Furthermore, some students may not feel any motivation for the English class, regardless of the teacher’s efforts to engage them in the class.